2022
DOI: 10.1590/0100-29452022832
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of rootstocks on the juice grape ‘BRS Magna’ grown in a Brazilian semi-arid region

Abstract: Rootstocks are widely used in viticulture worldwide and can affect the yield components and quality of grapes and their juices and wines. The aim of the present study was to determine the effect of the rootstock on the yield performance and physical and physical-chemical traits of ‘BRS Magna’ juice grapes grown in the Submédio do Vale do São Francisco. The study was performed over six production cycles in the period from 2015 to 2019 in the Bebedouro experimental field of Embrapa Semiárido in Petrolina, PE, Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
0
0
Order By: Relevance
“…The results obtained in this trial showed that the rootstock affected each table grape cultivar in a different way, confirming a genotype-dependent response already shown in different studies conducted on table grape (Leão et al 2020a(Leão et al , 2020b, juice (Leão et al 2022), and wine Chaves 2019, 2021)…”
Section: Resultssupporting
confidence: 86%
“…The results obtained in this trial showed that the rootstock affected each table grape cultivar in a different way, confirming a genotype-dependent response already shown in different studies conducted on table grape (Leão et al 2020a(Leão et al , 2020b, juice (Leão et al 2022), and wine Chaves 2019, 2021)…”
Section: Resultssupporting
confidence: 86%
“…The higher vigour expressed by 'IAC 572 Jales' in 'BRS Magna' may explain the higher yields obtained on this rootstock (Table 2). In another study, the IAC 572 rootstock promoted a 61% increase in the productivity of 'BRS Magna', with significant responses in the other production components Cunha;Souza, 2022), and was also superior for 'Moscato Embrapa' Feldberg, 2019) and 'Isabel' (Sato et al, 2009).…”
Section: Resultsmentioning
confidence: 96%